Necesidad de insertar en el art. Innumerado 6…(131) del código de la niñez y adolescencia, un literal de prohibición, para las actoras que tengan mas de tres causas diferentes de alimentos constando a partir del nivel 2 de la tabla de pensiones alimenticias, por existir un abuso de derecho - Jiménez Fernández, Daniel Alejandro (2016)
In our society it is common to hear that child support money is not intended for the well-being of the minor, but for the whim and vanity of their mothers, it is evident that there are many responsible mothers who look after the child's well-being; But that there are people who neglect the best interest of the child and make bad use of dietary prescription. The development of the present investigative work was proposed with the purpose of improving the legal regulations in Ecuador, as to the interest of raising money using a right. The pension table is a tool that determines the economic income of people according to their financial needs, but when someone makes use of the base and is an economic partner when the society, students and law students of the Lady of Justice there is no Arbitrarily unbalanced to the abusive application of a right. Social justice in a set of policies that have the purpose of resolving situations in which inequality and exclusion in the social group of a particular group of people arises. The mission of the laws implanted in a social state of rights and obligations is through them, the State is manifested resolving situations of inequality and the use of a right, situations that help society overcome and educate about the Importance and Respect that must be had to the life itself and foreign of each of the inhabitants that conform this society.